Dishonesty is contagious: investigating the domino effect of dysfunctional customer behaviorsDishonesty is contagious: investigating the domino effect of dysfunctional customer behaviors - Denise Telli; Lélis Balestrin Espartel Lélis Balestrin Espartel; Clecio Falcao Araujo; Kenny Basso (RAE: Revista de Administração de Empresas, 2020)
The interaction between dysfunctional customers and other customers can cause the domino effect (i.e., the dissemination of a dysfunctional client’s behavior to other nearby clients). However, it is not understood if this effect will manifest under certain levels of damage to the company. This study thus aims to verify if the amount of damage from the dysfunctional behavior can affect the probability of the domino effect. Through five experimental studies, we prove that the amount of damage influences the likelihood of dysfunctional behavior replication. Moreover, we found that this effect is explained by the acceptability of the dysfunctional behavior. We also identify that a consumer’s ethics level, perception of risk in replicating the behavior, and social distance acts as boundary conditions of the amount of damage effect on the probability of replicating the dysfunctional behavior.